Prevalence and Associated Risk Factors of Ankle Sprains in Maldivian Basketball Players - Layan, Ali Raheed; Maruthey, Nithiyah; Shalini, Sunmuganathan; Vinodhkumar, Ramalingam (INTI International University, 2023)
Introduction: Basketball players must perform jumps with both feet off the ground in the game, and they frequently land off balance and sustain ankle injuries. Despite the fact that the ankle supports the entire body's weight and has a wide range of motion, it is a frequently injured joint. Objective: In order to prevent recurrent ankle sprains and secondary consequences, the objective of this study is to identify the prevalence, risk factors and preferred treatment for ankle sprains among Maldivian basketball players. Methodology: A questionnaire was provided to the basketball players in the greater Male' region in the Maldives which helped obtain the necessary information to perform the study. Prevalence was analysed by frequency and the significance of risk factors was analysed using the Chi-Square Test on SPSS version 26. Results: In total, 92.7% of the 193 basketball players had an ankle sprain. Age, frequency of playing per week, player's position, and injury mechanism were identified as significant risk factors. Majority of the participants (62.6%) preferred the RICE (Rest, Ice, Compression, Elevation) approach for treating ankle sprains, followed by visits to physiotherapy clinics (14.5%) and hospitals (22.9%). Participants with prior educational experience in injury prevention made up 27.4% of the group. Conclusions: The results revealed a high prevalence of ankle sprains among basketball players from the Maldives Male' region, with age, weekly playing frequency, injury mechanism, and player position serving as important risk factors. This study provides an opportunity to start a conversation amongst athletes, coaches, and medical professionals because the majority of the participants lacked prior knowledge about injury prevention. Future intervention studies can be carried out to lessen the frequency and seriousness of ankle sprains in Maldivian basketball players.